Climate change, sustainability and anesthesiology practice: A national survey among anesthesiologists and nurse anesthetists in Norway - Espen Lindholm; Johanne Hegde; Cathrine Saltnes; Ann-Chatrin Leonardsen; Erlend Tuseth Aasheim (The Journal of Climate Change and Health, 2023)
Background: In the face of climate change the health sector will need to tackle both the increasing consequences for health worldwide and to reduce its own carbon footprint, which is estimated at 4.4% of global emissions. Raising the voice of health professionals has been identified as paramount to achieving the wide-scale and urgent response required to limit the consequences of climate change for health. Among health professionals, anesthetic practitioners are ideally placed to lead the way given that they make daily decisions regarding anesthetic gasses with a considerable footprint on climate and the environment. Methods: Here, we describe a cross-sectional nationwide survey among 3,300 anesthesiologists and nurse anesthetists in Norway, focusing on climate change, health, and sustainable anesthetic care. Responses were tabulated and characterized using descriptive statistics. Results: A large majority of the responding anesthesiologists and nurse anesthetists (n = 697, response rate 21.1%) agreed or strongly agreed that the world is facing a climate crisis; that nurses and doctors have a particular responsibility to warn about health threats; and that health organizations should limit their impact on climate and the environment. We found that desflurane is still widely used in Norway, despite its high climate footprint. We also identified several barriers to development of sustainable anesthetic care, including a lack of easy access to waste management systems, an absence of guidelines which promote sustainable care, and inadequate means for disposal of drug residues. Conclusions: Alongside other surveys, the present survey identifies safe and feasible adjustments to anesthetic practice which can give substantial emission reductions, pave the way for a wider health sector response, and yield considerable benefits to planetary health.